Calidad del agua y composición de la estructura de las comunidades de macroinvertebrados acuáticos en la microcuenca del río Quevedo, provincia de los Ríos, Ecuador - Vera Mesías, Bianca Daniela (2021)
This research was carried out in the micro-basin of the river Quevedo, Ecuador, with the purpose of evaluating the quality and composition of the structure of aquatic macroinvertebrates and its relationship with the uses of agricultural land, forest, mine, grassland and urban. During the months of December to August 2021, 180 samples were carried out at 30 stations, where ecosystem diversity indices were applied, and physicochemical parameters were supplemented by the biotic index of water quality BMWP- Cr, and river habitat indices (IHF), and river forest quality (QBR). 4562 specimens were collected during the rainy season, in 14 orders, 51 families and 89 genres, being the most representative genres Xiphocentron, Baetodes, Vacuperinus. Unlike the dry season with a total of 3769 specimens, distributed in 11 orders, 29 families and 37 genres, the most represented being the genres Baetodes, Pentaneura. In addition, forest land use showed greater dominance according to the Simpson 1-D Dominance index, unlike other land uses evaluated shows a greater wealth of species. As for the water quality obtained through the application of the BMWP-Cr biotic index between times, forest land use has an excellent level of water quality, unlike other soil uses which reflect moderate water quality during the rainy season, while in the dry season, all uses of soils have a water quality level that goes from regular to bad. As for the Channonica Correspondence (ACC) analysis, during the rainy season, it was shown that the genus Polycentropus is influenced by pH, and the genres Xiphocentron and Baetodes are sensitive to Temperature (°C), on the other hand, during the dry season the genus Brachydiplacinae. Keywords: Specimens, ecosystem diversity, taxonomic diversity, BMWP-Cr index.